THE FUNCTIONS OF LANDSCAPE IN SCHOOL LEARNING PROCESS - Mohamed Ali, Salina; Othman, Noriah; Abdul Latif, Faridatul Akma; Awang, Abd. Hair; Rostam, Katiman (PLANNING MALAYSIA, 2020)
This article seeks to identify the function of the schools’ landscapes in the learning process. For this study, primary data were collected through field observations using a checklist. 104 schools within the Klang Valley-Langat area were randomly selected. Structured interview sessions were conducted with school managers and secondary data were obtained from various agencies. Results showed that the function of landscapes in assisting learning was at a high score (47.1%). Scores of rural schools were at 51.6 percent ahead of urban schools (45.2 %). There was a significant relationship between the function of landscapes assisting in the learning process and academic achievement at the school level at 0.01 with a Chi-square value of 35.993. Pearson product-moment correlation test results showed a significant correlation in weak and moderate levels of landscape functions assisting in the process of learning and academic achievements. This proved that the landscape had an important role in the learning process. It is hoped that this study will create awareness among the school’s community.